1996
DOI: 10.1159/000189048
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Attenuates Proteinuria and Glomerular Injury in Unilaterally Nephrectomized Female Sprague-Dawley Rats

Abstract: To determine the contribution of the ovary to the development of glomerulosclerosis, we investigated the effect of ovariectomy on glomerulosclerosis, using the unilaterally nephrectomized (Nx) female Sprague-Dawley rat. At 6 weeks of age, groups 2 and 3 underwent unilateral right nephrectomy and group 3 was simultaneously ovariectomized, while group 1 underwent a sham operation. Body weight, blood pressure, urinary protein, serum albumin, cholesterol, blood urea nitrogen and serum creatinine were checked every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The effect of OVX on the course of nephropathy is controversial since it can be modified by many factors, such as age, race, sex, and experimental model of nephropathy used [30, 31, 32, 33, 34, 35, 36, 37]. Previous studies have shown that in addition to estrogens, growth hormone plays an important role in the course of drug-induced nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of OVX on the course of nephropathy is controversial since it can be modified by many factors, such as age, race, sex, and experimental model of nephropathy used [30, 31, 32, 33, 34, 35, 36, 37]. Previous studies have shown that in addition to estrogens, growth hormone plays an important role in the course of drug-induced nephropathy.…”
Section: Discussionmentioning
confidence: 99%